Efecto bactericida in vitro de Piper aduncum sobre streptococcus pyogenes - Benites Rodríguez, Alondra Nathalie (2017)
Objective: The principal objective of these investigation was to evaluate, in vitro, bactericidal effect of the ethanolic extract of Piper aduncum (matico) on Streptococcus pyogenes Group A. The ethanolic extract of Piper aduncum was prepared in five differents concentrations: 5%, 25%, 50%, 75% and 100%; also Penicillin of 10 IU was use as control. Methods: The Kirby Bauer (disc diffusion) method and the minimum inhibitory concentration (IMC) were used to evaluate the antibacterial activity of Piper aduncum on Streptococcus pyogenes Group A. Results: When comparing the inhibition halos according to the Duraffourd scale, Streptococcus pyogenes was highly sensitive to the five concentrations of the ethanolic extract of Piper aduncum like Penicillin but there isn´t significantly different between concentrations. Evaluating MIC, growth of S. pyogenes was inhibit by every kind of concentrations, also all the concentrations show a bactericidal effect. Conclusions: It was determined that the ethanolic extract of Piper aduncum (matico) has bactericidal effect in vitro on the growth of Streptococcus Pyogenes of group A